Renal resistive index and long-term outcome in patients with coronary artery disease - Wybraniec, Maciej T.; Bożentowicz-Wikarek, Maria; Olszanecka-Glinianowicz, Magdalena; Chudek, Jerzy; Mizia-Stec, Katarzyna (BMC cardiovascular disorders, 2020)
Background The study aimed to evaluate the application of intra-renal Doppler flow indices for the prediction of major adverse cardiac and cerebrovascular events (MACCE) during 24-month follow-up in patients with coronary artery disease (CAD) subject to coronary angiography (CA). Methods This prospective study comprised 111 consecutive patients with stable and unstable CAD (68.5% men; median age 65 years), referred for CA. Ultrasonographic parameters of intra-renal blood flow in arcuate/interlobular arteries, including renal resistive index (RRI) and pulsatility index (RPI), were acquired directly before and 1 h after the procedure. Endpoint of MACCE (cardiovascular death, myocardial infarction, myocardial revascularization or stroke) were recorded during 24-month follow-up. Results MACCE occurred in 14 patients (12.6%). Patients with MACCE had more diffuse CAD reflected by Syntax score (23.6 vs.14.4 pts., p = 0.02), higher platelet level (242.4 vs. 207.2 × 1000/μl, p = 0.01), higher rate of left main CAD (42.9% vs.5.2%, p < 0.001) and left ventricular ejection fraction < 50% (50% vs.23.7%, p = 0.045). Patients with MACCE had higher pre-procedural (0.68 ± 0.06 vs. 0.62 ± 0.06, p < 0.001) and post-procedural RRI (0.72 ± 0.06 vs.0.66 ± 0.06, p = 0.01), but comparable RPI ( p = 0.63 and p = 0.36, respectively). Cox proportional hazards model revealed that pre-procedural RRI (OR = 1.11 per 0.01; p = 0.02) and left main CAD (OR = 5.75, p = 0.002) were the only independent predictors of MACCE occurrence. Receiver operator characteristic curve analysis revealed that preprocedural RRI > 0.645 accurately predicted the composite endpoint (AUC = 0.78, p = 0.001) and identified patients with impaired 24-month prognosis according to Kaplan-Meier curve (log-rank p < 0.001). Conclusions Increased pre-procedural RRI, together with left main CAD, are associated with worse 24-month prognosis in patients with CAD referred for CA.